PENGARUH LINGKUNGAN KERJA, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT GELINDO GARMENTAMA PADA DEPARTEMEN QC - Jerisna, Jimjim; Sumawidjaja, Riyandi Nur (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to evaluate the relationship between Work Environment, Motivation, Work Discipline, and Employee Performance in the QC Department of PT Gelindo Garmentama and to determine the extent to which these variables influence Employee Performance. Using a quantitative method with a descriptive and verificative approach, the study collected primary and secondary data through documentation. The entire population, consisting of 80 respondents, was taken as a sample using a total sampling method. Data analysis involved descriptive techniques, classical assumption tests, multiple regression, and hypothesis testing, including both partial and simultaneous analysis. Descriptive analysis showed that Employee Performance, Work Environment, Motivation, and Work Discipline scored 1.241, 820, 1.374, and 1.215, respectively, all of which fall into the high category. The research findings confirm that Work Environment, Motivation, and Work Discipline significantly affect Employee Performance, both individually (partially) and collectively (simultaneously).